Sulfide-based inorganic solid electrolyte materials, solid electrolytes, solid electrolyte membranes and lithium-ion batteries

By adjusting the peak-area ratio of the PS4 and P2S6 glass structures in the 31P-NMR spectrum of the sulfide-based inorganic solid electrolyte material, the problem of insufficient ion conductivity of existing materials is solved, and the effect of high ion conductivity is achieved.

CN116583973BActive Publication Date: 2025-02-14FURUKAWA COMPANY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180079980.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-30
Filing Date
2021-11-12
Publication Date
2025-02-14
Estimated Expiration
2041-11-12

AI Technical Summary

Technical Problem

The existing sulfide-based inorganic solid electrolyte materials still have room for improvement in ion conductivity, and it is difficult to achieve high ion conductivity.

Method used

When the sum of the areas of peaks from the PS4 structure is set to 1 in the 31P-NMR spectrum, the sum of the areas of peaks from the P2S6 glass structure is increased to more than 0.1, and the raw material composition and manufacturing method are optimized to improve the ion conductivity .

Benefits of technology

The high ion conductivity of sulfide-based inorganic solid electrolyte materials is achieved, and the electrochemical performance of lithium-ion batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116583973B_ABST
    Figure CN116583973B_ABST
Patent Text Reader

Abstract

A sulfide-based inorganic solid electrolyte material comprising Li, P and S as constituent elements, wherein 31 In the spectrum obtained by P-NMR measurement, when the total area of ​​the peaks derived from the PS4 structure is set to 1, the total area of ​​the peaks derived from the P2S6 glass structure is greater than 0.1.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a sulfide-based inorganic solid electrolyte material, a solid electrolyte, a solid electrolyte membrane and a lithium ion battery. Background Art

[0002] Generally, lithium-ion batteries are used as power sources for small portable devices such as mobile phones and notebook computers. In addition, recently, lithium-ion batteries have begun to be used as power sources for electric vehicles, power storage, and the like in addition to small portable devices.

[0003] Currently, commercially available lithium-ion batteries use electrolytes containing flammable organic solvents.

[0004] On the other hand, research is being conducted on lithium-ion batteries (hereinafter also referred to as all-solid-state lithium-ion batteries) in which the electrolyte is replaced with a solid electrolyte and the battery is made fully solid. Since all-solid-state lithium-ion batteries do not contain flammable organic solvents in the battery, it is believed that the safety device is simplified and the manufacturing cost and productivity are excellent.

[0005] As a solid electrolyte material used for the solid electrolyte, for example, a sulfide-based inorganic solid electrolyte material is known.

[0006] As a specific prior art of solid electrolyte materials, Patent Documents 1 and 2 are known which focus on the use of 31 P-NMR measurement obtains the spectrum of the inorganic solid electrolyte material.

[0007] Patent Document 1 describes a solid electrolyte that satisfies all of the following conditions.

[0008] As constituent components, lithium, phosphorus, and sulfur are contained.

[0009] The following formula (A) is satisfied.

[0010] Li a P c S d X e (A)

[0011] [(In formula (A), a to e represent the composition ratio of each element, and a:c:d:e satisfies 1 to 9:1:3 to 7:0 to 9. X is 1.]

[0012] exist 31 In P-NMR, there is a peak (first peak) in the region of 83.0 ppm to 88.0 ppm, and there is no peak outside the region of 83.0 ppm to 88.0 ppm, or even if there is a peak, the peak intensity ratio to the first peak is 0.5 or less.

[0013] The ionic conductivity is 5×10-4 S / cm or more.

[0014] When 0.1 g of the solid electrolyte was placed in a 100 mL container and air having a humidity of 80 to 90% was passed through the container at 500 mL / min for 60 minutes, the average hydrogen sulfide concentration in the air was 200 ppm or less.

[0015] Patent Document 2 describes a sulfide solid electrolyte material containing phosphorus and sulfur. 31 In the spectrum obtained by P-NMR measurement, the peak appearing in the range of above 87.5 ppm and below 88.5 ppm is defined as the first peak, and in this spectrum, the peak appearing in the range of above 84.2 ppm and 85.2 ppm is defined as the second peak, and when the ratio of the integrated intensity of the first peak to the integrated intensity of the second peak is expressed as x:1-x, 0.00926≤x≤0.37.

[0016] Prior art literature

[0017] Patent Literature

[0018] Patent Document 1: Japanese Patent No. 6077740.

[0019] Patent document 2: Japanese Patent Application Publication No. 2019-3927. Summary of the invention

[0020] Problems to be solved by the invention

[0021] One of the properties required of solid electrolyte materials is high ion conductivity.

[0022] According to the findings of the present inventors, the ion conductivity of conventional sulfide-based inorganic solid electrolyte particles still has room for improvement.

[0023] The present invention has been made in view of the above circumstances. One object of the present invention is to provide sulfide-based inorganic solid electrolyte particles having high ion conductivity.

[0024] Means for solving problems

[0025] The present inventors have completed the invention provided below and solved the above-mentioned problems.

[0026] According to the present invention, there is provided a sulfide-based inorganic solid electrolyte material comprising Li, P and S as constituent elements, wherein 31 In the spectrum obtained by P-NMR measurement, when the total sum of the areas of the peaks derived from the PS4 structure is defined as 1, the total sum of the areas of the peaks derived from the P2S6 glass structure is 0.1 or more.

[0027] Furthermore, according to the present invention, there is provided a solid electrolyte comprising the above-mentioned sulfide-based inorganic solid electrolyte material.

[0028] Furthermore, according to the present invention, there is provided a solid electrolyte membrane comprising the above-mentioned solid electrolyte as a main component.

[0029] In addition, according to the present invention, a lithium ion battery is provided, which is a lithium ion battery having a positive electrode including a positive electrode active material layer, an electrolyte layer and a negative electrode including a negative electrode active material layer, and at least one of the positive electrode active material layer, the electrolyte layer and the negative electrode active material layer contains the above-mentioned inorganic solid electrolyte material.

[0030] Effects of the Invention

[0031] According to the present invention, sulfide-based inorganic solid electrolyte particles having high ion conductivity are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a cross-sectional view showing an example of the structure of a lithium ion battery.

[0033] Figure 2 The sulfide-based inorganic solid electrolyte material of Example 1 31 P-NMR spectrum. DETAILED DESCRIPTION

[0034] Next, refer to the attached Figure 1 Embodiments of the present invention will be described.

[0035] The drawings are for illustration purposes only, and the shapes, dimensional ratios, etc. of the components in the drawings do not necessarily correspond to actual items.

[0036] In the present specification, unless otherwise specified, the expression "X to Y" in the description of a numerical range means greater than or equal to X and less than or equal to Y. For example, "1 to 5 mass %" means "greater than or equal to 1 mass % and less than or equal to 5 mass %".

[0037] In the description of groups (atomic groups) in this specification, the description without substitution or unsubstituted includes both unsubstituted and substituted groups. For example, "alkyl" includes not only alkyl groups without substitution (unsubstituted alkyl groups) but also alkyl groups with substitution (substituted alkyl groups).

[0038] The expression "(meth)acrylic acid" in this specification represents a concept including both acrylic acid and methacrylic acid. The same applies to similar expressions such as "(meth)acrylate".

[0039] <Sulfide-based inorganic solid electrolyte materials>

[0040] The sulfide-based inorganic solid electrolyte material of the present embodiment contains Li, P, and S as constituent elements.

[0041] By subjecting the sulfide-based inorganic solid electrolyte material of this embodiment to 31 In the spectrum obtained by P-NMR measurement, when the total sum of the areas of the peaks derived from the PS4 structure is defined as 1, the total sum of the areas of the peaks derived from the P2S6 glass structure is 0.1 or more.

[0042] The present inventors have studied the improvement of the ion conductivity of sulfide-based inorganic solid electrolyte materials from various viewpoints. As a result, it has been found that 31 In the spectrum obtained by P-NMR measurement, the area of ​​the peak derived from the P2S6 glass structure seems to be correlated with the ion conductivity.

[0043] Based on this finding, the inventors conducted further research and found that when the total area of ​​the peaks from the PS4 structure is used as a reference, the ion conductivity is improved when the area of ​​the peaks from the P2S6 glass structure is large to a certain extent.

[0044] Therefore, the inventors improved the raw material composition and the manufacturing method, thereby newly manufacturing " 31 A sulfide-based inorganic solid electrolyte material having a value of "0.1 or more when the total area of ​​peaks derived from a PS4 structure is set to 1 in a spectrum obtained by P-NMR measurement". Moreover, the ion conductivity can be improved.

[0045] (“PS4 structure” includes both PS4 crystalline structure and PS4 glass structure)

[0046] The reason why the sulfide-based inorganic solid electrolyte material of the present embodiment exhibits good ion conductivity can be explained as follows. For the sake of caution, the following description includes speculations, and the present invention is not limited to the following description.

[0047] Theoretically, since the ionic conductivity of a crystalline structure is higher than that of a glass structure, it is believed that the ionic conductivity will be improved if all sulfide-based inorganic solid electrolyte materials are crystalline structures only. However, in actual systems, the movement of Li ions is inhibited at the interface between crystalline structures due to lattice mismatch.

[0048] In order to suppress the decrease in ion conductivity caused by this "lattice mismatch", it is believed that it is effective to embed the "gaps" between the crystalline structures with a glass structure. In this embodiment, it is believed that "the sum of the areas of the peaks from the P2S6 glass structure is greater than 0.1" indicates that there is an amount of P2S6 glass between the crystalline structures sufficient to improve the mobility of Li ions.

[0049] In addition, the “area of ​​the peak from the PS4 structure”, “area of ​​the peak from the P2S6 glass structure”, etc. are calculated by converting the peaks from the PS4 structure into the P2S6 glass structure using a Gaussian function. 31 The NMR spectrum obtained by P-NMR measurement is obtained by "waveform separation". Waveform separation can be performed, for example, using commercially available software that can perform curve fitting of various spectral data. As software capable of curve fitting, there can be cited software attached to the NMR device and software sold separately from the NMR device. As the former, there is ALICE2 from JOEL. In addition, as the latter, software such as OriginPro and IgorPro are very famous.

[0050] In Patent Document 1, there is no record of 31 P-NMR spectrum is separated and analyzed by waveform separation. 31 There is no mention of the area of ​​the peaks in the P-NMR spectrum that are derived from the P2S6 glass structure. 31 The present inventors' original idea is to separate the waveform of P-NMR spectrum and "precisely" study it, and on this basis, focus on the area of ​​the peak derived from the P2S6 glass structure relative to the area of ​​the peak derived from the PS4 structure.

[0051] In addition, in this embodiment, the chemical shift of each chemical species can be the value in the following table (unit: ppm). That is, when separating the obtained NMR spectrum waveform into peaks corresponding to each chemical species, it is preferable to use a Gaussian function showing a maximum value within the numerical range shown in the following table.

[0052] Table 1

[0053]

[0054] The sulfide-based inorganic solid electrolyte material of this embodiment can be obtained by using appropriate raw materials and a suitable manufacturing method. Preferred materials and manufacturing methods will be described in detail later. For example, (i) P2S5 having a P content greater than 27.87 mass % specified by stoichiometry can be used as a raw material; (ii) the molar ratio of each raw material is adjusted so that the composition of the final sulfide-based inorganic solid electrolyte material is Li 10 P3S 12 or its vicinity; (iii) performing appropriate annealing treatment, etc. By paying attention to this point, the sulfide-based inorganic solid electrolyte material of the present embodiment can be easily manufactured.

[0055] The description of the sulfide-based inorganic solid electrolyte material according to the present embodiment will be continued.

[0056] (About NMR spectroscopy)

[0057] As mentioned above, 31 When the sum of the areas of the peaks from the PS4 structure (both the PS4 crystalline structure and the PS4 glass structure) in the P-NMR spectrum is set to 1, the sum of the areas of the peaks from the P2S6 glass structure is greater than 0.1. This value is preferably greater than 0.15, more preferably greater than 0.25. In addition, for the upper limit of this value, for example, less than 2.0, preferably less than 1.0. It is believed that the appropriate value refers to the presence of an appropriate amount of P2S6 glass in the "gap" between the crystalline structures. That is, by appropriately adjusting this value, the ionic conductivity can be further improved.

[0058] exist 31 In the P-NMR spectrum, when the sum of the peak areas from the PS4 glass structure is set to 1, the sum of the peak areas from the P2S6 glass structure is preferably 0.15 or more, more preferably 0.25 or more. In addition, the upper limit of this value is, for example, 3.0 or less, preferably 1.0 or less. The details are not clear, and it is speculated that the sulfide-based inorganic solid electrolyte material includes both the P2S6 glass structure and the PS4 glass structure as a glass structure, and, by the appropriate ratio of these glass structures, various types of lattice mismatches between the crystalline structures can be embedded in the glass structure. Moreover, as a result, it is believed that a further improvement in ionic conductivity is sometimes achieved.

[0059] exist 31 In the P-NMR spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is defined as 1, the total sum of the areas of the peaks derived from the PS4 crystal structure is preferably 0.3 to 1, and more preferably 0.3 to 0.5.

[0060] As described above, it is believed that the mobility of Li ions is improved by the presence of an appropriate amount of glass structure between the crystal structures. It is speculated that this value of 0.3 to 1 means that an appropriate amount of glass structure exists between the crystal structures at the cutout of the PS4 composition.

[0061] exist 31 In the P-NMR spectrum, when the total sum of the areas of the peaks derived from the PS4 structure is defined as 1, the total sum of the areas of the peaks derived from the P2S7 glass structure is usually 0.05 to 0.25, preferably 0.05 to 0.2.

[0062] exist 31 In the P-NMR spectrum, when the total sum of the peak areas derived from the PS4 structure is defined as 1, the total sum of the peak areas derived from the P2S7 crystal structure is usually 0.05 to 0.25, preferably 0.05 to 0.2.

[0063] exist 31In the P-NMR spectrum, when the total sum of the peak areas derived from the PS4 structure is defined as 1, the total sum of the peak areas derived from the P2S6 crystal structure is usually 0.005 to 0.02, preferably 0.01 to 0.1.

[0064] exist 31 In the P-NMR spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is defined as 1, the total sum of the areas of the peaks derived from the P2S7 glass structure is usually 0.05 to 0.3, preferably 0.08 to 0.25.

[0065] exist 31 In the P-NMR spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is defined as 1, the total sum of the areas of the peaks derived from the P2S7 crystal structure is usually 0.05 to 0.3, preferably 0.08 to 0.25.

[0066] exist 31 In the P-NMR spectrum, when the total area of ​​the peaks derived from the PS4 glass structure is set to 1, the total area of ​​the peaks derived from the P2S6 crystal structure is usually 0.01 to 0.2, preferably 0.01 to 0.15, and more preferably 0.01 to 0.1.

[0067] Sometimes, the ion conductivity can be further improved by appropriately adjusting the peak areas.

[0068] (For constituent elements and their composition)

[0069] The sulfide-based inorganic solid electrolyte material of the present embodiment contains Li, P, and S as constituent elements from the viewpoints of electrochemical stability, stability in water or air, and handleability.

[0070] In addition, the sulfide-based inorganic solid electrolyte material of the present embodiment, from the viewpoint of further improving lithium ion conductivity, electrochemical stability, stability in water or air, and handleability, the molar ratio Li / P of the Li content to the P content in the sulfide-based inorganic solid electrolyte material is preferably 1.0 to 5.0, more preferably 2.0 to 4.0, further preferably 2.5 to 3.8, further preferably 2.8 to 3.6, further preferably 3.0 to 3.5, further preferably 3.1 to 3.4, and particularly preferably 3.2 to 3.4.

[0071] In addition, the molar ratio S / P of the S content to the P content is preferably 2.0 to 6.0, more preferably 3.0 to 5.0, further preferably 3.5 to 4.5, further preferably 3.8 to 4.2, further preferably 3.9 to 4.1, and particularly preferably 4.0.

[0072] The contents of Li, P, and S in the sulfide-based inorganic solid electrolyte material can be determined by, for example, ICP emission spectrometry analysis or X-ray analysis.

[0073] The composition formula of the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably Li 10 P3S 12 As another way of expressing it, when manufacturing the sulfide-based inorganic solid electrolyte material of this embodiment, it is preferred to optimize the mixing ratio of each raw material so that the composition formula of the sulfide-based inorganic solid electrolyte material finally obtained is Li 10 P3S 12 or nearby.

[0074] (For particle size distribution)

[0075] The sulfide-based inorganic solid electrolyte material of the present embodiment is usually composed of particles from the viewpoint of applicability to lithium-ion batteries, etc. In another way of expressing it, the sulfide-based inorganic solid electrolyte material of the present embodiment is usually in the form of particles.

[0076] The ion conductivity may be further improved by appropriately designing the particle size distribution of particles constituting the sulfide-based inorganic solid electrolyte material.

[0077] For the particle size distribution, the median particle size d can be quantitatively calculated based on the number of particles. 50 As an indicator. 50 It is preferably 0.1 to 10 μm, and more preferably 0.1 to 6.0 μm. 50 If the contact area (interface) between particles is reduced, a better ion conductivity can be obtained. 50 If the particle size is not too large, it is difficult to generate gaps between particles, thus achieving better ion conductivity.

[0078] For example, the median particle size d can be obtained by (1) photographing particles with an electron microscope, (2) measuring the tangential diameter (Feret diameter) of each particle in the photographed image, and (3) plotting the tangential diameter (Feret diameter) of each particle as the horizontal axis and the frequency based on the number of particles as the vertical axis. 50 The calculation is based on the particle size distribution based on the number of particles.

[0079] (Other matters)

[0080] Generally, the sulfide-based inorganic solid electrolyte material of the present embodiment has excellent electrochemical stability. Electrochemical stability refers to the property of being difficult to oxidize and reduce in a wide voltage range, for example. More specifically, in the sulfide-based inorganic solid electrolyte material of the present embodiment, the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material measured under the conditions of a temperature of 25°C, a scanning voltage range of 0 to 5V, and a voltage scanning rate of 5mV / second is preferably 0.50μA or less, more preferably 0.20μA or less, further preferably 0.10μA or less, further preferably 0.05μA or less, and particularly preferably 0.03μA or less.

[0081] When the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is equal to or less than the above upper limit, oxidative decomposition of the sulfide-based inorganic solid electrolyte material in the lithium ion battery can be suppressed, which is preferable.

[0082] The lower limit of the maximum value of the oxidative decomposition current of the sulfide-based inorganic solid electrolyte material is not particularly limited, but is, for example, 0.0001 μA or more.

[0083] The sulfide-based inorganic solid electrolyte material of the present embodiment can be used for any purpose requiring lithium ion conductivity. Among them, the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably used for lithium ion batteries. More specifically, it is used for the positive electrode active material layer, the negative electrode active material layer, the electrolyte layer, etc. in the lithium ion battery. Furthermore, the sulfide-based inorganic solid electrolyte material of the present embodiment is suitable for constituting the positive electrode active material layer, the negative electrode active material layer, the solid electrolyte layer, etc. of an all-solid-state lithium ion battery, and is particularly suitable for constituting the solid electrolyte layer of an all-solid-state lithium ion battery.

[0084] An example of an all-solid-state lithium-ion battery to which the sulfide-based inorganic solid electrolyte material of the present embodiment is applied is a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are stacked in this order.

[0085] In addition, lithium ion conductivity can be used as a quantitative index of lithium ion conductivity. The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material of this embodiment is, for example, 1.0×10 -3 S / cm or more, preferably 1.5×10 - 3 S / cm or more. The higher the lithium ion conductivity, the better. In fact, the upper limit of lithium ion conductivity is, for example, 5.0×10 -3 S / cm, specifically 3.0×10 -3 S / cm, more specifically 2.0×10-3 S / cm. The lithium ion conductivity can be measured, for example, in the manner described in Examples described below.

[0086] (Method for producing inorganic solid electrolyte material)

[0087] The sulfide-based inorganic solid electrolyte material of the present embodiment can be obtained by a manufacturing method including the following steps (A), (B) and (C). In addition, as required, the manufacturing method of the sulfide-based inorganic solid electrolyte material of the present embodiment preferably further includes the following step (D). In this case, step (C) may be performed before step (D), may be performed after step (D), or may be performed at the same time.

[0088] Step (A): a step of preparing a raw material composition.

[0089] Step (B): A step of mechanically treating a raw material composition of a sulfide-based inorganic solid electrolyte material to vitrify the raw material composition while chemically reacting the raw material composition, thereby obtaining a glass-state sulfide-based inorganic solid electrolyte material.

[0090] Step (C): a step of subjecting the obtained sulfide-based inorganic solid electrolyte material to classification treatment.

[0091] Step (D): a step of heating (annealing) the obtained glassy sulfide-based inorganic solid electrolyte material to crystallize at least a portion of it.

[0092] These steps are described in detail below.

[0093] Step (A) of preparing a raw material composition

[0094] First, raw materials are appropriately mixed to prepare a raw material composition of a sulfide-based inorganic solid electrolyte material. Here, the mixing ratio of each raw material in the raw material composition is adjusted so that the obtained sulfide-based inorganic solid electrolyte material has a desired composition ratio.

[0095] The raw material composition of the sulfide-based inorganic solid electrolyte material typically contains lithium sulfide and phosphorus sulfide, and preferably further contains lithium nitride.

[0096] As described above, the molar ratio of each raw material is preferably adjusted so that the composition of the final sulfide-based inorganic solid electrolyte material becomes Li 10 P3S 12 In other words, the composition of the raw materials is preferably adjusted so that the molar amount of Li relative to the molar amount of P (Li / P) is 3.2 to 3.4, and the molar amount of S relative to the molar amount of P (S / P) is 3.9 to 4.1.

[0097] In addition, Li 10 P3S 12 It is a composition rich in lithium. Therefore, by using lithium nitride as a raw material, it is easy to optimize the composition.

[0098] The method of mixing the raw materials is not particularly limited as long as it is a mixing method that can uniformly mix the raw materials. For example, mixing can be performed using a ball mill, a bead mill, a vibration mill, a percussion pulverizer, a mixer (a pug mixer, a ribbon mixer, a drum mixer, a roller mixer, a V-type mixer, etc.), a kneader, a twin-screw kneader, a jet mill, etc. As long as it is at the laboratory level, mixing using a mortar such as agate or alumina may be performed.

[0099] Mixing conditions such as stirring speed, treatment time, temperature, reaction pressure, and gravitational acceleration applied to the mixture when mixing the raw materials can be appropriately determined according to the amount of the mixture to be treated.

[0100] The lithium sulfide used as a raw material is not particularly limited, and commercially available lithium sulfide can be used. For example, lithium sulfide obtained by reacting lithium hydroxide with hydrogen sulfide can also be used. From the viewpoint of obtaining a high-purity sulfide-based inorganic solid electrolyte material and suppressing side reactions, it is preferred to use lithium sulfide with less impurities.

[0101] In this embodiment, the lithium sulfide also includes lithium polysulfide. As the lithium sulfide, Li2S is preferred.

[0102] As described above, as the phosphorus sulfide used as a raw material, P2S5 having a P content greater than 27.87 mass % as specified by stoichiometry is preferably used as a raw material. Although the details are not clear, it is presumed that by using such P2S5 "containing excess P" as a raw material, in steps (B) and (D), not only ordered crystals but also more disordered glass than crystals are generated, thereby generating an appropriate amount of P2S6 glass structure.

[0103] From the viewpoint of further improving the availability of the raw materials and the ion conductivity of the final sulfide-based inorganic solid electrolyte material, the P content in the raw material P2S5 is preferably 28.0 to 28.3% by mass.

[0104] As a raw material, lithium nitride can be used. Here, since nitrogen in lithium nitride is discharged into the system in the form of N2, by using lithium nitride as a raw material, that is, an inorganic compound, for a sulfide-based inorganic solid electrolyte material including Li, P, and S as constituent elements, only the Li composition can be increased.

[0105] There is no particular limitation on the lithium nitride that can be used. Commercially available lithium nitride (e.g., Li3N, etc.) can be used, for example, lithium nitride obtained by reacting metallic lithium (e.g., Li foil) with nitrogen can be used. From the perspective of obtaining a high-purity solid electrolyte material and suppressing side reactions, it is preferred to use lithium nitride with few impurities.

[0106] Step (B) of obtaining a glassy sulfide-based inorganic solid electrolyte material

[0107] By mechanically treating the raw material composition obtained in step (A), lithium sulfide, phosphorus sulfide, and preferably lithium nitride as raw materials are chemically reacted and vitrified, thereby obtaining a glassy sulfide-based inorganic solid electrolyte material.

[0108] In the mechanical treatment, two or more inorganic compounds are mechanically collided to chemically react and vitrify them. As the mechanical treatment, for example, mechanochemical treatment can be cited. Mechanochemical treatment is a method of vitrifying the target composition while applying mechanical energy such as shear force and collision force.

[0109] In the step (B), the mechanochemical treatment is preferably a dry mechanochemical treatment from the viewpoint of easily achieving an environment in which moisture and oxygen are removed at a high level.

[0110] By applying mechanochemical treatment, each raw material can be mixed while being crushed into fine particles. Therefore, the contact area of ​​each raw material can be increased. Therefore, the reaction of each raw material can be promoted. Therefore, the sulfide-based inorganic solid electrolyte material of this embodiment can be obtained more efficiently.

[0111] Mechanochemical treatment refers to a method of vitrifying while applying mechanical energy such as shear force, collision force or centrifugal force to the mixed object. As a device (vitrification device) for vitrification by mechanochemical treatment, a ball mill, a bead mill, a vibration mill, a turbine grinder, a mechanical fusion machine, a disc mill, a roller mill and other crushing / dispersing machines can be cited; a rotating / strike crushing device composed of a mechanism composed of a combination of rotation (shear stress) and impact (compression stress) represented by a rock drill, a vibration drill, an impact driver, etc.; a high-pressure grinding roller, etc. Among them, from the viewpoint of being able to efficiently generate very high impact energy, a ball mill and a bead mill are preferred, and a ball mill is particularly preferred. In addition, from the viewpoint of excellent continuous productivity, a roller mill is preferred; a rotating / strike crushing device composed of a mechanism composed of a combination of rotation (shear stress) and impact (compression stress) represented by a rock drill, a vibration drill, an impact driver, etc.; a high-pressure grinding roller; a roller-type vertical mill, a ball-type vertical mill and other vertical mills, etc.

[0112] In this embodiment, it is particularly preferred to use a ball mill to perform step (B). More specifically, it is preferred to use zirconia balls with a diameter of 5 to 50 mm to perform the mechanochemical treatment for a total of about 10 to 1500 hours. When a ball mill is used to perform step (B), during this process, powder attached to the inner wall and balls of the ball mill device can be scraped off, and the scraped powder can be put back into the ball mill to restart the mechanochemical treatment.

[0113] It is preferred that step (B) be performed under an environment in which the amount of water and oxygen present and the inflow thereof are suppressed to a high level. Thus, the contact of the raw material composition with water and oxygen can be suppressed to a high level.

[0114] An environment in which the amount of water and oxygen present and the inflow thereof are suppressed at a high level can be formed by, for example, the following method.

[0115] First, a mixing container and a sealed container for a vitrification device are placed in a glove box, and then a high-purity dry argon gas, dry nitrogen gas or other inert gas obtained by a gas purification device is injected into the glove box multiple times (preferably 3 times or more) and vacuum degassed. Here, in the glove box after the above operation, a high-purity dry argon gas, dry nitrogen gas or other inert gas is circulated by the gas purification device to adjust the oxygen concentration and water concentration to preferably 1.0 ppm or less, more preferably 0.8 ppm or less, and further preferably 0.6 ppm or less, respectively.

[0116] Next, lithium sulfide and phosphorus sulfide are added to the mixing container in the glove box, and then, a raw material composition is prepared by mixing (referring to step (A)). Here, lithium sulfide and phosphorus sulfide are added to the mixing container in the glove box according to the following steps. First, with the door inside the main body of the glove box closed, lithium sulfide and phosphorus sulfide are added to the side box of the glove box. Next, the side box is injected with an inert gas such as high-purity dry argon or dry nitrogen introduced from the glove box multiple times (preferably 3 times or more) and vacuum degassed, then, the door inside the main body of the glove box is opened, lithium sulfide and phosphorus sulfide are placed in the mixing container inside the main body of the glove box, and the mixing container is sealed.

[0117] Next, after lithium sulfide and phosphorus sulfide are mixed, the obtained raw material composition is taken out from the mixing container, transferred to a container for a vitrification device, and sealed.

[0118] By performing such an operation, the amount of water and oxygen present in the sealed container containing the raw material composition can be suppressed to a higher level than before. As a result, in step (B), an environment in which the amount of water and oxygen present can be suppressed to a high level can be formed.

[0119] Then, take out the sealed container in which the raw inorganic composition is placed from the glove box. Next, a sealed container is set in a vitrification device configured in an environment full of dry gases such as dry argon, dry nitrogen, dry air (for example, in a box full of dry argon, dry nitrogen, dry air, etc.), and vitrification is performed. Here, it is preferred that during the vitrification, a prescribed amount of dry gas is continuously introduced into an environment full of dry gas. By making such improvements, in step (B), an environment in which the inflow of moisture and oxygen is suppressed at a high level can be formed.

[0120] From the viewpoint of suppressing the inflow of moisture and oxygen into the sealed container at a high level and achieving higher airtightness, it is preferred to use a sealant with excellent sealing properties such as an O-ring or a ferrule seal on the lid of the sealed container.

[0121] In general, when X-ray diffraction analysis is performed using CuKα rays as a radiation source, if the diffraction peak from the raw material disappears or decreases, it can be determined that the raw inorganic composition is vitrified and the desired sulfide-based inorganic solid electrolyte material can be obtained.

[0122] In step (B), the vitrification treatment is preferably performed until the lithium ion conductivity of the sulfide-based inorganic solid electrolyte material is preferably 1.0×10 -4 S cm -1 More preferably, 2.0×10 -4 S cm -1 More preferably, 3.0×10 -4 S cm -1 More than 4.0×10 -4 S cm -1 As described above, a sulfide-based inorganic solid electrolyte material having even better lithium ion conductivity can be obtained.

[0123] Classification (Screening) Process (C)

[0124] The obtained sulfide-based inorganic solid electrolyte material is preferably subjected to classification treatment (screening). By performing this treatment, for example, d 50 .

[0125] The sulfide-based inorganic solid electrolyte material may be further subjected to a pulverization treatment to adjust the particle size, etc. As a specific method for the pulverization treatment, a known pulverization method such as a jet mill, a mortar, a rotary mill, a coffee grinder, etc. can be used.

[0126] From the viewpoint of preventing contact with moisture in the air, the step (C) is preferably performed under an inert gas atmosphere or a vacuum atmosphere.

[0127] Step (D) of crystallizing at least a portion of the sulfide-based inorganic solid electrolyte material

[0128] In the present embodiment, it is preferred to carry out a process of crystallizing at least a portion of the sulfide-based inorganic solid electrolyte material. In step (D), by heating (annealing) the sulfide-based inorganic solid electrolyte material in a glass state, at least a portion of the sulfide-based inorganic solid electrolyte material is crystallized, thereby generating a sulfide-based inorganic solid electrolyte material in a glass ceramic state (also referred to as crystallized glass). By appropriately selecting the heating conditions, the ratio of each glass structure and each crystal structure in the sulfide-based inorganic solid electrolyte material can be adjusted. Moreover, a sulfide-based inorganic solid electrolyte material having further excellent lithium ion conductivity can be obtained.

[0129] In other words, from the viewpoint of excellent lithium ion conductivity, the sulfide-based inorganic solid electrolyte material of the present embodiment is preferably in a glass ceramic state (crystallized glass state).

[0130] The temperature at which the glassy sulfide-based inorganic solid electrolyte material is heated (annealed) is preferably 220 to 500°C, more preferably 250 to 350°C.

[0131] The heating (annealing) time of the glassy sulfide-based inorganic solid electrolyte material is not particularly limited as long as it is a time for obtaining the desired glass-ceramic sulfide-based inorganic solid electrolyte material, and the time is, for example, 0.5 to 24 hours, preferably 1 to 18 hours, more preferably 1 to 15 hours, and even more preferably 1 to 10 hours.

[0132] The heating method is not particularly limited, and for example, a method using a sintering furnace can be mentioned. The heating conditions such as the temperature and time can be appropriately adjusted to optimize the characteristics of the sulfide-based inorganic solid electrolyte material.

[0133] The heating (annealing) of the sulfide-based inorganic solid electrolyte material in a glassy state is preferably performed in an inert gas environment. Thus, the degradation (e.g., oxidation) of the sulfide-based inorganic solid electrolyte material can be prevented. As inert gases, for example, argon, helium, nitrogen, etc. can be cited. In order to prevent impurities from mixing into the product, the higher the purity of these inert gases, the more preferred. In addition, in order to avoid contact with moisture, the dew point is preferably below -70°C, and particularly preferably below -80°C.

[0134] The method of introducing the inert gas is not particularly limited as long as the system is filled with an inert gas atmosphere, and examples thereof include a method of purging the inert gas and a method of continuously introducing a predetermined amount of inert gas.

[0135] In order to obtain the sulfide-based inorganic solid electrolyte material of the present embodiment, it is preferable to appropriately adjust the above-mentioned steps. However, the method for producing the sulfide-based inorganic solid electrolyte material of the present embodiment is not limited to the above-mentioned method, and the sulfide-based inorganic solid electrolyte material of the present embodiment can be obtained by appropriately adjusting various conditions.

[0136] <Solid electrolyte>

[0137] The solid electrolyte of the present embodiment includes the above-mentioned sulfide-based inorganic solid electrolyte material of the present embodiment.

[0138] The solid electrolyte of the present embodiment may contain, as a component other than the sulfide-based inorganic solid electrolyte material of the present embodiment, for example, a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above, or may not contain it within the scope not impairing the purpose of the present invention.

[0139] The solid electrolyte of the present embodiment may or may not contain a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment described above. As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, there is no particular limitation as long as it has ion conductivity and insulation, and a solid electrolyte material commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials that are different from the sulfide-based inorganic solid electrolyte material of the present embodiment can be cited; and organic solid electrolyte materials such as polymer electrolytes can be cited.

[0140] As the aforementioned sulfide-based inorganic solid electrolyte material different from the sulfide-based inorganic solid electrolyte material of the present embodiment, for example, there can be cited Li2S-P2S5 material, Li2S-SiS2 material, Li2S-GeS2 material, Li2S-Al2S3 material, Li2S-SiS2-Li3PO4 material, Li2S-P2S5-GeS2 material, Li2S-Li2O-P2S5-SiS2 material, Li2S-GeS2-P2S5-SiS2 material, Li2S-SnS2-P2S5-SiS2 material, Li2S-P2S5-Li3N material, Li2S 2+X-P4S3 material, Li2S-P2S5-P4S3 material, etc. These may be used alone or in combination of two or more.

[0141] Among them, Li2S-P2S5 materials are preferred from the viewpoint of excellent lithium ion conductivity and stability in a wide voltage range without causing decomposition, etc. Here, for example, Li2S-P2S5 materials refer to inorganic materials obtained by chemically reacting an inorganic composition containing at least Li2S (lithium sulfide) and P2S5 with each other through mechanical treatment.

[0142] Here, in the present embodiment, lithium sulfide also includes lithium polysulfide.

[0143] Examples of the oxide-based inorganic solid electrolyte material include NASICON-type (La 0.5+x Li 0.5-3x )TiO3 and other perovskite types, Li2O-P2O5 materials, Li2O-P2O5-Li3N materials, etc.

[0144] As other lithium-based inorganic solid electrolyte materials, for example, LiPON, LiNbO3, LiTaO3, Li3PO4, LiPO 4-x N x (x is 0<x≤1), LiN, LiI, LISICON, etc.

[0145] Furthermore, glass ceramics obtained by precipitating crystals of these inorganic solid electrolytes can also be used as an inorganic solid electrolyte material.

[0146] As the organic solid electrolyte material, for example, a polymer electrolyte such as a dry polymer electrolyte or a gel electrolyte can be used.

[0147] As the polymer electrolyte, an electrolyte generally used for lithium ion batteries can be used.

[0148] <Solid electrolyte membrane>

[0149] The solid electrolyte membrane of the present embodiment includes a solid electrolyte as a main component, and the solid electrolyte contains the sulfide-based inorganic solid electrolyte material of the present embodiment described above.

[0150] The solid electrolyte membrane of the present embodiment is used to constitute a solid electrolyte layer of an all-solid-state lithium-ion battery, for example.

[0151] As an example of an all-solid-state lithium-ion battery to which the solid electrolyte membrane of the present embodiment is applied, there can be mentioned a battery in which a positive electrode, a solid electrolyte layer, and a negative electrode are sequentially stacked. In this case, the solid electrolyte layer is composed of a solid electrolyte membrane.

[0152] The average thickness of the solid electrolyte membrane of the present embodiment is preferably 5 μm or more and 500 μm or less, more preferably 10 μm or more and 200 μm or less, and further preferably 20 μm or more and 100 μm or less. When the average thickness of the solid electrolyte membrane is above the lower limit, the loss of solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed. In addition, when the average thickness of the solid electrolyte membrane is below the upper limit, the impedance of the solid electrolyte membrane can be further reduced. As a result, the battery characteristics of the obtained all-solid-state lithium-ion battery can be further improved.

[0153] The solid electrolyte membrane of the present embodiment is preferably a pressurized body of a particulate solid electrolyte comprising the sulfide-based inorganic solid electrolyte material of the present embodiment. That is, it is preferred that the particulate solid electrolyte is pressurized to form a solid electrolyte membrane having a predetermined strength due to the anchoring effect between the solid electrolyte materials.

[0154] By forming a press-molded body, the solid electrolytes are bonded to each other, and the strength of the obtained solid electrolyte membrane is further improved. As a result, the loss of solid electrolytes and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed.

[0155] When the solid electrolyte membrane as a whole is set to 100% by mass, the content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the solid electrolyte membrane of the present embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. Thus, the contact between the solid electrolytes is improved, and the interfacial contact resistance of the solid electrolyte membrane can be reduced. As a result, the lithium ion conductivity of the solid electrolyte membrane can be further improved. Moreover, by using such a solid electrolyte membrane with excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be further improved.

[0156] The upper limit of the content of the sulfide-based inorganic solid electrolyte material of the present embodiment in the solid electrolyte membrane of the present embodiment is not particularly limited, and is, for example, 100 mass % or less.

[0157] The planar shape of the solid electrolyte membrane is not particularly limited and can be appropriately selected according to the shapes of the electrodes and the current collector. The planar shape can be, for example, a rectangle.

[0158] The solid electrolyte membrane of the present embodiment may contain a binder resin. When the binder resin is contained, the content thereof is preferably less than 0.5% by mass, more preferably less than 0.1% by mass, further preferably less than 0.05% by mass, and further preferably less than 0.01% by mass, when the solid electrolyte membrane as a whole is set to 100% by mass. In addition, it is further preferred that the solid electrolyte membrane of the present embodiment does not substantially contain a binder resin, and most preferably does not contain a binder resin.

[0159] Thus, the contact between the solid electrolytes is improved, and the interface contact resistance of the solid electrolyte membrane can be reduced. As a result, the lithium ion conductivity of the solid electrolyte membrane can be further improved. Moreover, by using such a solid electrolyte membrane with excellent lithium ion conductivity, the battery characteristics of the obtained all-solid-state lithium ion battery can be improved.

[0160] For the sake of caution, "substantially free of binder resin" means that the binder resin may be contained to the extent that the effect of the present embodiment is not impaired. In addition, when an adhesive resin layer is provided between the solid electrolyte layer and the positive electrode or the negative electrode, the adhesive resin from the adhesive resin layer present near the interface between the solid electrolyte layer and the adhesive resin layer is excluded from the "binder resin in the solid electrolyte membrane".

[0161] The binder resin is a binder generally used in lithium ion batteries to bind inorganic solid electrolyte materials, and includes, for example, polyvinyl alcohol, poly(meth)acrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, and the like.

[0162] For example, the solid electrolyte membrane of the present embodiment can be obtained by (i) first depositing a particulate solid electrolyte in a film-like manner on the cavity surface of a mold or on the surface of a substrate, and (ii) then pressurizing the deposited solid electrolyte in a film-like manner.

[0163] There is no particular limitation on the method of pressurizing the solid electrolyte in (ii) above. For example, when the particulate solid electrolyte is deposited on the surface of the cavity of the mold, pressurization based on the mold and the die can be used; when the particulate solid electrolyte is deposited on the surface of the substrate, pressurization based on the mold and the die, roller pressing, flat plate pressing, etc. can be used. The pressure for pressurizing the solid electrolyte is, for example, 10 to 500 MPa.

[0164] If necessary, the inorganic solid electrolyte deposited in a film form may be pressurized and heated at the same time. As long as the heating and pressurization are performed, the fusion and bonding between the solid electrolytes will be caused, and the strength of the obtained solid electrolyte membrane will be further improved. As a result, the loss of solid electrolyte and the generation of cracks on the surface of the solid electrolyte membrane can be further suppressed. The temperature for heating the solid electrolyte is, for example, 40 to 500°C.

[0165] <Lithium-ion battery>

[0166] Figure 1 1 is a cross-sectional view showing an example (lithium ion battery 10 ) of the structure of the lithium ion battery according to the present embodiment.

[0167] The lithium ion battery 100 includes, for example, a positive electrode 110 including a positive electrode active material layer 101, an electrolyte layer 120, and a negative electrode 130 including a negative electrode active material layer 103. Moreover, at least one of the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 contains the sulfide-based inorganic solid electrolyte material of the present embodiment. In addition, it is preferred that the positive electrode active material layer 101, the negative electrode active material layer 103, and the electrolyte layer 120 all contain the sulfide-based inorganic solid electrolyte material of the present embodiment.

[0168] In this embodiment, unless otherwise specified, a layer including a positive electrode active material is referred to as a positive electrode active material layer 101 .

[0169] As required, the positive electrode 110 may include a current collector 105 in addition to the positive electrode active material layer 101, or may not include the current collector 105. In addition, in this embodiment, unless otherwise specified, the layer including the negative electrode active material is referred to as the negative electrode active material layer 103. As required, the negative electrode 130 may include a current collector 105 in addition to the negative electrode active material layer 103, or may not include the current collector 105.

[0170] The shape of the lithium ion battery 100 is not particularly limited, and may be a cylindrical shape, a coin shape, a rectangular shape, a film shape, or any other shape.

[0171] The lithium ion battery 100 is manufactured by a generally known method, for example, by stacking the positive electrode 110, the electrolyte layer 120, and the negative electrode 130 to form a cylindrical, coin-shaped, rectangular, film-shaped, or other arbitrary shape, and sealing a non-aqueous electrolyte solution as needed.

[0172] (positive electrode)

[0173] There is no particular limitation on the material constituting the positive electrode 110, and a positive electrode commonly used in lithium-ion batteries can be used. There is no particular limitation on the method for manufacturing the positive electrode 110, and it can be manufactured according to a generally known method. For example, it can be obtained by forming a positive electrode active material layer 101 containing a positive electrode active material on the surface of a current collector 105 such as aluminum foil.

[0174] The thickness and density of the positive electrode active material layer 101 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.

[0175] The positive electrode active material layer 101 contains a positive electrode active material.

[0176] There is no particular limitation on the positive electrode active material, and commonly known positive electrode active materials can be used. For example, lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), solid solution oxide (Li2MnO3-LiMO2 (M=Co, Ni, etc.)), lithium-manganese-nickel oxide (LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2), olivine-type lithium phosphorus oxide (LiFePO4) and other composite oxides; conductive polymers such as polyaniline and polypyrrole; sulfide-based positive electrode active materials such as Li2S, CuS, Li-Cu-S compounds, TiS2, FeS, MoS2, Li-Mo-S compounds, Li-Ti-S compounds, Li-VS compounds, and Li-Fe-S compounds; materials with sulfur as active material such as sulfur-impregnated acetylene black, sulfur-impregnated porous carbon, and mixed powders of sulfur and carbon. These positive electrode active materials can be used alone or in combination of two or more.

[0177] Among them, from the viewpoint of having a higher discharge capacity density and better cycle characteristics, a sulfide-based positive electrode active material is preferred, and one or more selected from a Li-Mo-S compound, a Li-Ti-S compound, and a Li-VS compound is more preferred.

[0178] Here, the Li—Mo—S compound contains Li, Mo, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing molybdenum sulfide and lithium sulfide as raw materials with each other through mechanical treatment.

[0179] The Li—Ti—S compound contains Li, Ti, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing titanium sulfide and lithium sulfide as raw materials by mechanical treatment.

[0180] The Li—VS compound contains Li, V, and S as constituent elements, and can be generally obtained by chemically reacting an inorganic composition containing vanadium sulfide and lithium sulfide as raw materials with each other through mechanical treatment.

[0181] The positive electrode active material layer 101 may contain, or may not contain, one or more materials selected from a binder resin, a thickener, a conductive aid, a solid electrolyte material, etc., as components other than the above-mentioned positive electrode active material. The following describes each material such as a binder resin, a thickener, a conductive aid, and a solid electrolyte material.

[0182] The positive electrode active material layer 101 may contain a binder resin having a function of binding the positive electrode active materials to each other and binding the positive electrode active material to the current collector 105 .

[0183] As long as the binder resin is a common binder resin that can be used in lithium ion batteries, there is no particular limitation. For example, polyvinyl alcohol, poly(meth)acrylic acid, carboxymethyl cellulose, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber, polyimide, etc. can be cited. These binders can be used alone or in combination of two or more.

[0184] From the viewpoint of ensuring the fluidity of the slurry suitable for coating, the positive electrode active material layer 101 may also include a thickener. As a thickener, there is no particular limitation as long as it is a common thickener that can be used for lithium ion batteries. For example, cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose and their ammonium salts and water-soluble polymers such as alkali metal salts, polycarboxylic acids, polyethylene oxide, polyvinyl pyrrolidone, poly (meth) acrylates, polyvinyl alcohol, etc. can be cited. Thickeners can be used alone or in combination of two or more.

[0185] From the viewpoint of improving the conductivity of the positive electrode 110, the positive electrode active material layer 101 may include a conductive aid. As the conductive aid, there is no particular limitation as long as it is a common conductive aid that can be used in lithium ion batteries. For example, carbon black such as acetylene black and Ketjen black, carbon materials such as gas-phase carbon fiber, etc. can be cited. When using a conductive aid, one type can be used alone, or two or more types can be used in combination.

[0186] The positive electrode 110 may contain a solid electrolyte including the sulfide-based inorganic solid electrolyte material of the present embodiment described above, or may contain a solid electrolyte including a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment. As a solid electrolyte material of a different type from the sulfide-based inorganic solid electrolyte material of the present embodiment, there is no particular limitation as long as it has ion conductivity and insulation, and a solid electrolyte material commonly used in lithium-ion batteries can be used. For example, inorganic solid electrolyte materials such as sulfide-based inorganic solid electrolyte materials, oxide-based inorganic solid electrolyte materials, and other lithium-based inorganic solid electrolyte materials; and organic solid electrolyte materials such as polymer electrolytes can be cited. More specifically, the inorganic solid electrolyte materials cited in the description of the solid electrolyte of the present embodiment can be used.

[0187] Since the mixing ratio of each material in the positive electrode active material layer 101 is appropriately determined according to the use of the battery, etc., it is not particularly limited and can be set according to generally known information.

[0188] (negative electrode)

[0189] There is no particular limitation on the material constituting the negative electrode 130, and materials commonly used in lithium-ion batteries can be used. There is no particular limitation on the method for manufacturing the negative electrode 130, and it can be manufactured according to a generally known method. For example, it can be obtained by forming a negative electrode active material layer 103 containing a negative electrode active material on the surface of a current collector 105 such as copper.

[0190] The thickness and density of the negative electrode active material layer 103 are appropriately determined according to the intended use of the battery, and therefore are not particularly limited and can be set according to generally known information.

[0191] The negative electrode active material layer 103 contains a negative electrode active material.

[0192] The negative electrode active material is not particularly limited as long as it is a common negative electrode active material that can be used for the negative electrode of a lithium ion battery. For example, carbonaceous materials such as natural graphite, artificial graphite, resin carbon, carbon fiber, activated carbon, hard carbon, and soft carbon; metal materials based on lithium, lithium alloys, tin, tin alloys, silicon, silicon alloys, gallium, gallium alloys, indium, indium alloys, aluminum, and aluminum alloys; conductive polymers such as polyacene, polyacetylene, and polypyrrole; lithium titanium composite oxides (such as Li4Ti5O 12 ) etc. These negative electrode active materials may be used alone or in combination of two or more.

[0193] The negative electrode active material layer 103 is not particularly limited, and as components other than the negative electrode active material, for example, it may also contain one or more materials selected from a binder resin, a thickener, a conductive aid, a solid electrolyte material, etc. These materials are not particularly limited, and for example, the same materials as those used in the positive electrode 110 can be cited.

[0194] Since the mixing ratio of each material in the negative electrode active material layer 103 is appropriately determined according to the use of the battery, etc., it is not particularly limited and can be set according to generally known information.

[0195] (Electrolyte layer)

[0196] The electrolyte layer 120 is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103 .

[0197] Examples of the electrolyte layer 120 include a layer in which a separator is impregnated with a non-aqueous electrolyte solution and a solid electrolyte layer containing a solid electrolyte.

[0198] The separator is not particularly limited as long as it electrically insulates the positive electrode 110 from the negative electrode 130 and has a function of allowing lithium ions to pass therethrough. For example, a porous film can be used.

[0199] As the porous film, a microporous polymer film is preferably used, and examples of the material include polyolefin, polyimide, polyvinylidene fluoride, polyester, etc. In particular, a porous polyolefin film is preferred, and specific examples include a porous polyethylene film, a porous polypropylene film, and the like.

[0200] The non-aqueous electrolyte impregnated in the separator is an electrolyte obtained by dissolving an electrolyte in a solvent. As the electrolyte, any known lithium salt can be used, as long as it is selected according to the type of active material. For example, LiClO4, LiBF6, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiB 10 Cl 10 , LiAlCl4, LiCl, LiBr, LiB(C2H5)4, CF3SO3Li, CH3SO3Li, LiCF3SO3, LiC4F9SO3, Li(CF3SO2)2N, lower fatty acid carboxylic acid lithium, etc.

[0201] As long as the solvent for dissolving the electrolyte is a solvent commonly used as a liquid for dissolving the electrolyte, there is no particular limitation. For example, carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (MEC), and vinylene carbonate (VC); lactones such as γ-butyrolactone and γ-valerolactone; ethers such as trimethoxymethane, 1,2-dimethoxyethane, diethyl ether, 2-ethoxyethane, tetrahydrofuran, and 2-methyltetrahydrofuran; sulfoxides such as dimethyl sulfoxide; 1,3-dioxolane, 4-methyl-1,3- Oxolanes such as dioxolane; nitrogen-containing compounds such as acetonitrile, nitromethane, formamide, and dimethylformamide; organic acid esters such as methyl formate, methyl acetate, ethyl acetate, butyl acetate, methyl propionate, and ethyl propionate; triesters of phosphate, diglyme; triglyme; sulfolanes such as sulfolane and methyl sulfolane; oxazolidinones such as 3-methyl-2-oxazolidinone; sultones such as 1,3-propane sultone, 1,4-butane sultone, and naphthalene sultone, etc. These materials may be used alone or in combination of two or more.

[0202] The solid electrolyte layer is a layer formed between the positive electrode active material layer 101 and the negative electrode active material layer 103, and is a layer formed of a solid electrolyte containing a solid electrolyte material. As long as the solid electrolyte contained in the solid electrolyte layer has lithium ion conductivity, there is no particular limitation. However, in this embodiment, it is preferably a solid electrolyte containing a sulfide-based inorganic solid electrolyte material of this embodiment.

[0203] As long as the content of the solid electrolyte in the solid electrolyte layer of the present embodiment is a ratio that can obtain the desired performance, there is no particular limitation, for example, it is 10 volume % or more and 100 volume % or less, preferably 50 volume % or more and 100 volume % or less. In particular, in the present embodiment, it is preferred that the solid electrolyte layer is composed only of a solid electrolyte containing the sulfide-based inorganic solid electrolyte material of the present embodiment.

[0204] The solid electrolyte layer of the present embodiment may also contain a binder resin. By containing a binder resin, a flexible solid electrolyte layer can be obtained. As the binder resin, for example, fluorine-containing binders such as polytetrafluoroethylene and polyvinylidene fluoride can be cited. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less, preferably 0.1 μm or more and 300 μm or less.

[0205] The embodiments of the present invention are described above, but these are examples of the present invention, and various configurations other than the above can also be adopted. In addition, the present invention is not limited to the above-mentioned embodiments, and modifications and improvements within the scope of achieving the purpose of the present invention are also included in the present invention.

[0206] Example

[0207] Embodiments of the present invention will be described in detail based on Examples and Comparative Examples. However, for the sake of caution, the present invention is not limited to Examples alone.

[0208] <Manufacturing of sulfide-based inorganic solid electrolyte materials>

[0209] (Example 1)

[0210] First, as raw materials, Li2S (manufactured by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (manufactured by Perimeter Solutions Co., Ltd.), and Li3N (manufactured by Furukawa Metals Co., Ltd.) were prepared respectively. For P2S5, a product with a P content of 28.1% by mass was selected from some P2S5 products with different batch numbers obtained from Perimeter Solutions Co., Ltd. For the determination of the P content, an ICP emission spectrophotometer (manufactured by Seiko Instruments Inc., SPS3000) was used for determination by ICP emission spectrophotometry.

[0211] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder were accurately weighed (Li2S: P2S5: Li3N = 27:9:2 (molar ratio)). Then, these powders were mixed in an agate mortar for 10 minutes. In this way, a mixed powder was obtained.

[0212] Next, 500 g of the mixed powder was weighed and placed in an alumina container (internal volume 5.0 L) together with 7500 g of 25 mm φ zirconium oxide balls and 700 g of 10 mm φ zirconium oxide balls. Next, the mixture was pulverized and mixed in a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).

[0213] Next, scrape the powder attached to the inner wall of the container and the ball after the pulverization and mixing. Next, put the powder and the ball into the same container again and pulverize and mix them with a ball mill (rotation speed 100 rpm) for the same time as before. Repeat the operation from scraping to pulverization until the cumulative time reaches 700 hours. Then, a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0214] The pulverization and mixing (mechanochemical treatment) is performed under an environment in which the presence and inflow of moisture and oxygen are suppressed to a high level.

[0215] Next, the glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours. Thus, a glassy ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0216] The obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified with a sieve having an opening of 20 μm to remove coarse particles.

[0217] As described above, the sulfide-based inorganic solid electrolyte material is produced.

[0218] The composition of the obtained sulfide-based inorganic solid electrolyte material was confirmed to be Li by ICP emission spectrometry using an ICP emission spectrometer (SPS3000 manufactured by Seiko Instruments Inc.). 10 P3S 12 .

[0219] (Example 2)

[0220] First, as raw materials, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (produced by Peripheral Solutions Co., Ltd.), and Li3N (produced by Furukawa Metals Co., Ltd.) were used. For P2S5, a product with a P content of 28.0 mass % was selected from a number of P2S5 products with different batch numbers obtained from Peripheral Solutions Co., Ltd. (the method for determining the P content was the same as in Example 1).

[0221] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder were accurately weighed (Li2S: P2S5: Li3N = 27:9:2 (molar ratio)). Then, these powders were mixed in an agate mortar for 10 minutes. In this way, a mixed powder was obtained.

[0222] Next, 500 g of the mixed powder was weighed and placed in an alumina container (internal volume 5.0 L) together with 7500 g of 25 mm φ zirconium oxide balls and 700 g of 10 mm φ zirconium oxide balls. Next, the mixture was pulverized and mixed in a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).

[0223] Next, scrape the powder attached to the inner wall of the container and the ball after the pulverization and mixing. Next, put the powder and the ball into the same container again and pulverize and mix them with a ball mill (rotation speed 100 rpm) for the same time as before. Repeat the operation from scraping to pulverization until the cumulative time reaches 700 hours. Then, a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0224] Next, the glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours. Thus, a glassy ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0225] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified with a sieve having an opening of 20 μm to remove coarse particles.

[0226] As described above, the sulfide-based inorganic solid electrolyte material is produced.

[0227] The composition of the obtained sulfide-based inorganic solid electrolyte material was confirmed to be Li by ICP emission spectrometry using an ICP emission spectrometer (SPS3000 manufactured by Seiko Instruments Inc.). 10 P3S 12 .

[0228] (Example 3)

[0229] First, as raw materials, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (produced by Kanto Chemical Co., Ltd.), and Li3N (produced by Furukawa Metals Co., Ltd.) were used respectively. For P2S5, P2S5 having a P content of 27.9 mass % greater than 27.87 mass % was selected from some P2S5 products with different batch numbers obtained from Kanto Chemical Co., Ltd. (the method for determining the P content was the same as in Example 1).

[0230] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder were accurately weighed (Li2S: P2S5: Li3N = 27:9:2 (molar ratio)). Then, these powders were mixed in an agate mortar for 10 minutes. In this way, a mixed powder was obtained.

[0231] Next, 500 g of the mixed powder was weighed and placed in an alumina container (internal volume 5.0 L) together with 7500 g of 25 mm φ zirconium oxide balls and 700 g of 10 mm φ zirconium oxide balls. Next, the mixture was pulverized and mixed in a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).

[0232] Next, scrape the powder attached to the inner wall of the container and the ball after the pulverization and mixing. Next, put the powder and the ball into the same container again and pulverize and mix them with a ball mill (rotation speed 100 rpm) for the same time as before. Repeat the operation from scraping to pulverization until the cumulative time reaches 700 hours. Then, a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0233] Next, the glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours. Thus, a glassy ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0234] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified with a sieve having an opening of 20 μm to remove coarse particles.

[0235] As described above, the sulfide-based inorganic solid electrolyte material is produced.

[0236] The composition of the obtained sulfide-based inorganic solid electrolyte material was confirmed to be Li by ICP emission spectrometry using an ICP emission spectrometer (SPS3000 manufactured by Seiko Instruments Inc.). 10 P3S 12 .

[0237] (Comparative Example 1)

[0238] In Comparative Example 1, unlike Examples 1 to 3, Li3N was not used as a raw material to produce Li9P3S 12 The specific steps are as follows.

[0239] First, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%) and P2S5 (produced by Peripheral Solutions, Inc., P content 28.1% by mass, the P content was measured in the same manner as in Example 1) were prepared as raw materials.

[0240] Next, in an argon glove box, Li2S powder and P2S5 powder were accurately weighed (Li2S:P2S5=75:25 (molar ratio)). Then, these powders were mixed for 10 minutes in an agate mortar. In this way, a mixed powder was obtained.

[0241] Next, 500 g of the mixed powder was weighed and placed in an alumina container (internal volume 5.0 L) together with 7500 g of 25 mm φ zirconium oxide balls and 700 g of 10 mm φ zirconium oxide balls. Next, the mixture was pulverized and mixed in a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).

[0242] Next, scrape the powder attached to the inner wall of the container and the balls after the pulverization and mixing. Next, put the powder and the balls into the same container again and pulverize and mix them with a ball mill (rotation speed 100 rpm) for the same time as before. Repeat the operation from scraping to pulverization until the cumulative time reaches 700 hours. Next, the glassy sulfide-based inorganic solid electrolyte material (Li9P3S 12 ).

[0243] Next, the glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours. Thus, a glassy ceramic sulfide-based inorganic solid electrolyte material (Li9P3S 12 ).

[0244] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified with a sieve having an opening of 20 μm to remove coarse particles.

[0245] As described above, the sulfide-based inorganic solid electrolyte material is produced.

[0246] The composition of the obtained sulfide-based inorganic solid electrolyte material was confirmed to be Li9P3S by ICP emission spectrometry using an ICP emission spectrometer (SPS3000 manufactured by Seiko Instruments Inc.). 12 .

[0247] (Comparative Example 2)

[0248] In Comparative Example 2, unlike Examples 1 to 3, P2S5 with a low P content was used as a raw material. The specific steps are as follows.

[0249] First, as raw materials, Li2S (produced by Furukawa Metals Co., Ltd., purity 99.9%), P2S5 (produced by Peripheral Solutions Co., Ltd.), and Li3N (produced by Furukawa Metals Co., Ltd.) were prepared. For P2S5, a product with a P content of 27.7 mass % was selected from some P2S5 products with different batch numbers obtained from Peripheral Solutions Co., Ltd. (the method for determining the P content was the same as in Example 1).

[0250] Next, in an argon glove box, Li2S powder, P2S5 powder, and Li3N powder were accurately weighed (Li2S: P2S5: Li3N = 27:9:2 (molar ratio)). Then, these powders were mixed in an agate mortar for 10 minutes. In this way, a mixed powder was obtained.

[0251] Next, 500 g of the mixed powder was weighed and placed in an alumina container (internal volume 5.0 L) together with 7500 g of 25 mm φ zirconium oxide balls and 700 g of 10 mm φ zirconium oxide balls. Next, the mixture was pulverized and mixed in a ball mill (rotation speed 100 rpm) for 48 hours (mechanical chemical treatment).

[0252] Next, scrape the powder attached to the inner wall of the container and the ball after the pulverization and mixing. Next, put the powder and the ball into the same container again and pulverize and mix them with a ball mill (rotation speed 100 rpm) for the same time as before. Repeat the operation from scraping to pulverization until the cumulative time reaches 700 hours. Then, a glassy sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0253] Next, the glassy sulfide-based inorganic solid electrolyte material was annealed in argon at 300° C. for 7 hours. Thus, a glassy ceramic sulfide-based inorganic solid electrolyte material (Li 10 P3S 12 ).

[0254] Next, the obtained sulfide-based inorganic solid electrolyte material in a glass ceramic state was classified with a sieve having an opening of 20 μm to remove coarse particles.

[0255] As described above, the sulfide-based inorganic solid electrolyte material is produced.

[0256] The composition of the obtained sulfide-based inorganic solid electrolyte material was confirmed to be Li by ICP emission spectrometry using an ICP emission spectrometer (SPS3000 manufactured by Seiko Instruments Inc.). 10 P3S 12 .

[0257] <31 P-NMR measurement>

[0258] The sulfide-based inorganic solid electrolyte materials obtained in each of the Examples and Comparative Examples were used as samples and subjected to phosphorus 31 nuclear magnetic resonance spectroscopy analysis as follows. Next, waveform separation was performed.

[0259] The sample was filled in a 3.2 mm diameter sample tube in a glove bag purged with N2, placed in the device, and rotated (Magic Angle Spinning: MAS) at a magic angle (54.7°) relative to the external magnetic field for measurement.

[0260] Details of the NMR measurement conditions are as follows.

[0261] Observation frequency: 242.95MHz.

[0262] Pulse width: 90° pulse.

[0263] Pulse waiting time: 2800sec.

[0264] Cumulative number of times: 64 times.

[0265] Measurement mode: single pulse method.

[0266] MAS speed: 12kHz.

[0267] Standard substance: (NH4)2HPO4 1.33ppm.

[0268] Apparatus: JNM-ECA600, manufactured by JEOL Resonance Inc.

[0269] Use software that can carry out waveform separation, and by Gaussian function, the NMR spectrum waveform obtained is separated into the peak from PS4 glass structure, the peak from PS4 crystalline structure, the peak from P2S7 glass structure, the peak from P2S7 crystalline structure, the peak from P2S6 glass structure and the peak from P2S6 crystalline structure. Then, the area of ​​each Gaussian function is set to the sum of the area of ​​the peak from each structure. When the waveform is separated, the maximum position (equivalent to the chemical shift of each structure), the half-value width, and the maximum value of each Gaussian function are optimized so that the NMR spectrum obtained is reproduced as faithfully as possible. However, for the maximum position of each Gaussian function, it is optimized within the numerical range described in the above-mentioned table 1.

[0270] As a reference, the sulfide-based inorganic solid electrolyte material of Example 1 31 The P-NMR spectra (raw data and spectra after waveform separation) are shown in Figure 2 .

[0271] <Measurement of particle size / Calculation of particle size distribution>

[0272] The obtained SEM image of the sulfide-based inorganic solid electrolyte material was analyzed using the image processing software (free software, ImageJ, v1.52a) published by the National Institutes of Health. Then, the particle size distribution was calculated based on the analysis. Then, d 50 .

[0273] As a procedure, first, a carbon tape is attached to a sample stage of an SEM, and a trace amount of particles of a sulfide-based inorganic solid electrolyte material are attached to the carbon tape in a thin and widely scattered state.

[0274] Then, a SEM image of the sulfide-based inorganic solid electrolyte material is taken (resolution: 1280 horizontal × 960 vertical pixels). The obtained SEM image is read into ImageJ. Correction is performed according to the scale displayed in the SEM image. Then, the image is converted into a black and white binary image. At this time, a threshold is set to make the outline of the particles clear. When there are overlapping particles in the obtained black and white image, as an image processing based on ImageJ, the overlap between the particles is separated by the watershed method. In addition, as an image analysis based on ImageJ, a particle analysis is performed to obtain the measurement results of the particle size based on the Feret diameter. In each embodiment and comparative example, the particle sizes of more than 3,000 particles are measured.

[0275] The particle size distribution was obtained by reading the measured results of the particle size using the spreadsheet software EXCEL (registered trademark) of Microsoft Corporation. Next, the median particle size d was calculated based on the particle size distribution. 50 .

[0276] In all the examples and comparative examples, d 50 In the range of 0.1 to 10 μm.

[0277] <Evaluation: Measurement of lithium ion conductivity>

[0278] The lithium ion conductivity of the sulfide-based inorganic solid electrolyte material obtained in each of the Examples and Comparative Examples was measured by an alternating current impedance method.

[0279] Lithium ion conductivity was measured using a potentiostat / galvanostat SP-300 manufactured by Bio-Logic Inc. The sample size was 9.5 mm in diameter and 1.2 to 2.0 mm in thickness, and the measurement conditions were an applied voltage of 10 mV, a measurement temperature of 27.0°C, a measurement frequency range of 0.1 Hz to 7 MHz, and the electrode was a Li foil.

[0280] As a sample for measuring lithium ion conductivity, a plate-like sulfide-based inorganic solid electrolyte material having a diameter of 9.5 mm and a thickness of 1.2 to 2.0 mm was used. The plate-like sulfide-based inorganic solid electrolyte material was obtained by pressurizing 150 mg of the powdered sulfide-based inorganic solid electrolyte material obtained in each of the examples and comparative examples under the conditions of 270 MPa for 10 minutes using a pressurizing device.

[0281] Various information is summarized in Tables 2 and 3. Tables 2 and 3 summarize the information of Examples 1 to 3 and Comparative Examples 1 to 2, (i) Table 2 shows the peak area from the structure when the sum of the peak area from the PS4 structure (both the PS4 crystalline structure and the PS4 glass structure) is set to 1, and (ii) Table 3 shows the area from each structure when the sum of the peak area from the PS4 glass structure is set to 1.

[0282] Table 2

[0283]

[0284] Table 3

[0285]

[0286] As shown in Tables 2 and 3, 31 In the spectrum obtained by P-NMR measurement, when the sum of the areas of the peaks from the PS4 structure is set to 1, the sulfide-based inorganic solid electrolyte materials (Examples 1 to 3) whose sum of the areas of the peaks from the P2S6 glass structure is 0.1 or more show high lithium ion conductivity. On the other hand, the sulfide-based inorganic solid electrolyte materials (Comparative Examples 1 and 2) whose sum of the areas of the peaks from the P2S6 glass structure is less than 0.1 have poor lithium ion conductivity.

[0287] In addition, from the comparison between Examples 1 and 2 and Example 3, it was found that the lithium ion conductivity tended to be higher when the total area of ​​the peaks derived from the P2S6 glass structure was larger.

[0288] This application claims priority based on Japanese patent application No. 2020-197943, filed on November 30, 2020, and the entire contents of the Japanese patent application are incorporated herein into this application.

[0289] Description of Reference Numerals

[0290] 100: Lithium-ion battery.

[0291] 101: Positive electrode active material layer.

[0292] 103: Negative electrode active material layer.

[0293] 105: Current collector.

[0294] 110: Positive electrode.

[0295] 120: Electrolyte layer.

[0296] 130: Negative pole.

Claims

1. A sulfide-based inorganic solid electrolyte material, comprising Li, P and S as constituent elements, wherein: In passing 31 In the spectrum obtained by P-NMR measurement, when the sum of the areas of the peaks derived from the PS4 structure is set to 1, the sum of the areas of the peaks derived from the P2S6 glass structure is 0.1 or more. The sulfide-based inorganic solid electrolyte material has a molar ratio of Li content to P content (Li / P) of 3.2 or more and 3.4 or less, and a molar ratio of S content to P content (S / P) of 3.9 or more and 4.1 or less, The sulfide-based inorganic solid electrolyte material uses P2S5 having a P content greater than 27.87 mass % specified by stoichiometry as a raw material, and the molar ratio of each raw material is adjusted so that the composition of the final sulfide-based inorganic solid electrolyte material becomes Li 10 P3S 12 or nearby.

2. The sulfide-based inorganic solid electrolyte material according to claim 1, wherein In the spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is set to 1, the total sum of the areas of the peaks derived from the P2S6 glass structure is greater than or equal to 0.

15.

3. The sulfide-based inorganic solid electrolyte material according to claim 1, wherein In the above spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is defined as 1, the total sum of the areas of the peaks derived from the PS4 crystal structure is 0.3 to 1.

4. The sulfide-based inorganic solid electrolyte material according to claim 2, wherein In the above spectrum, when the total sum of the areas of the peaks derived from the PS4 glass structure is defined as 1, the total sum of the areas of the peaks derived from the PS4 crystal structure is 0.3 to 1.

5. The sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 4, wherein The lithium ion conductivity is 1.5×10 -3 S / cm or more.

6. The sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 4, wherein It is composed of particles with a median particle size of 0.1 to 10 μm.

7. The sulfide-based inorganic solid electrolyte material according to claim 5, wherein It is composed of particles with a median particle size of 0.1 to 10 μm.

8. Use of the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 7 in a lithium ion battery.

9. A solid electrolyte, wherein: The solid electrolyte includes the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 7.

10. A solid electrolyte membrane, wherein: The solid electrolyte membrane contains the solid electrolyte according to claim 9 as a main component.

11. The solid electrolyte membrane according to claim 10, wherein The solid electrolyte membrane is a press-molded body of the solid electrolyte in a particle form.

12. The solid electrolyte membrane according to claim 10 or 11, wherein: When the entire solid electrolyte membrane is taken as 100 mass %, the content of the binder resin in the solid electrolyte membrane is less than 0.5 mass %.

13. The solid electrolyte membrane according to claim 10 or 11, wherein When the entire solid electrolyte membrane is taken as 100 mass %, the content of the sulfide-based inorganic solid electrolyte material in the solid electrolyte membrane is 50 mass % or more.

14. The solid electrolyte membrane according to claim 12, wherein: When the entire solid electrolyte membrane is taken as 100 mass %, the content of the sulfide-based inorganic solid electrolyte material in the solid electrolyte membrane is 50 mass % or more.

15. A lithium ion battery comprising a positive electrode including a positive electrode active material layer, an electrolyte layer, and a negative electrode including a negative electrode active material layer, wherein: At least one of the positive electrode active material layer, the electrolyte layer, and the negative electrode active material layer contains the sulfide-based inorganic solid electrolyte material according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Sulfide solid electrolyte material and cell using the same

    JP2019003927A

  • Apparatus and method for monitoring

    JP2020197943A

  • Sulfide solid electrolyte material and battery containing the same

    CN109088092A

  • Sulfide-based inorganic solid electrolyte material, solid electrolyte, solid electrolyte membrane and lithium ion battery

    JP2020053219A

  • KR20200107396A